“Actually, they used to pay no notice of”: Soviet Law Enforcement and Gender-Related Violence Problem in Historical Sources - Kareniauskaitė, Monika (Genocidas ir rezistencija, 2019)
After occupation and annexation of Lithuania, soviet government started to reorganize such institution like police and courts. Repressed former juridical elite, qualified independent jurist were changes by unqualified immigrants or by other loyal to soviets persons. Soviet law enforcement bodies became marionette of system, tool of repressions and one of the institution that generated traumas. Precisely, this process is subject of our research and touches to the complex problem of soviet and nowadays- coersion against women-, let us to understand how subtile and unvisibly soviet terror mechanism worked. It incalcultated atrophy of humanism and civilness and indifferent to others pain.